2011
DOI: 10.1002/lary.21752
|View full text |Cite
|
Sign up to set email alerts
|

Selection and placement of oral ventilation tubes based on tracheal morphometry

Abstract: Selection of size and placement of ventilation tubes can be based on patient height. Considerable differences in the dimensions of ventilation tubes necessitate a height-based nomogram for evidence-based tube selection and placement. A uniform system of tube labeling based on biometric data is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 27 publications
(30 reference statements)
1
69
1
Order By: Relevance
“…Cases and controls did not differ with respect to weight (86.4 vs. 86.2 kg, P = .97) or in the average size of ETT used (7.7 ± 1.9 vs. 7.7 ± 0.4 mm, P = .59). When adjusted for appropriate ETT sizing utilizing a published nomogram for tracheal size, 42/106 (40%) of controls were appropriate, compared with only 19/77 (25%) of cases ( P = .22). Duration of intubation was not significantly longer in the PGS case group in univariate analysis (7 vs. 5 days; P = .31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases and controls did not differ with respect to weight (86.4 vs. 86.2 kg, P = .97) or in the average size of ETT used (7.7 ± 1.9 vs. 7.7 ± 0.4 mm, P = .59). When adjusted for appropriate ETT sizing utilizing a published nomogram for tracheal size, 42/106 (40%) of controls were appropriate, compared with only 19/77 (25%) of cases ( P = .22). Duration of intubation was not significantly longer in the PGS case group in univariate analysis (7 vs. 5 days; P = .31).…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of biologically plausible mechanisms that might explain an inverse relationship between height and risk of PGS. Anatomic studies have shown that airway diameter is proportional to an individual's height . It seems obvious that a shorter person would have smaller airway, and that a large ETT in a small airway (improperly sized) would increase the likelihood of mucosal injury and thus PGS.…”
Section: Discussionmentioning
confidence: 99%
“…13 Using Coordes and colleagues' nomogram, an average-size US woman (163 cm) would be assigned a 7.0 mm recommended ETT size, whereas an average US man (177 cm) would be assigned a recommended 8.0 mm ETT. We suggest that men of shorter stature may be best served by intubation with a smaller size ETT (7.0-7.5 mm), whereas tall males may accommodate a larger ETT if required.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The selection of ETT size for pediatric patients is well studied, and there are multiple guidelines and nomograms correlating the size of the trachea (and thus ideal ETT size) with readily measurable parameters such as weight and age of the patient. 13 Anecdotal evidence has suggested that height may correlate with tracheal diameter, 13,14 and in our clinical practice, ETT sizing has been informed by the patient's height (eg, shorter patients would be intubated with a smaller size ETT than a similar, taller patient). 3 Consequently, selection of adult ETT size is done arbitrarily and without a reliable assessment of the tracheal diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the typical ETT size used for an adult female is 7-8 mm and for the adult male is 8-8.5 mm (2,3). Inappropriate ETT sizing may lead to technical difficulties or undesired complications, such as subglottic/laryngeal edema, ischemia, ulceration, and subsequent stenosis (4) Several methods have been used to aid in determining the appropriate ETT size. One method entails using radiographs to measure the tracheal width (5).…”
Section: Introductionmentioning
confidence: 99%